2019
DOI: 10.1103/physrevlett.123.051103
|View full text |Cite
|
Sign up to set email alerts
|

Strong Constraints on Fuzzy Dark Matter from Ultrafaint Dwarf Galaxy Eridanus II

Abstract: predict that the abundance of halos in FDM is severely reduced relative to CDM for masses less than M cut ≈ 3 × 10 8 m −3/2 22

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
129
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(138 citation statements)
references
References 71 publications
8
129
1
Order By: Relevance
“…[21]. The implications of these fluctuations for local tracer velocities have been studied elsewhere [34] and they can provide a benchmark for comparing ULDM halo fluctuations to CDM substructure, as well as adding scatter to the expected velocity dispersion. We remark that these fluctuations are not captured by the semi-analytic model of ULDM halos, and that the consequences of this should be kept in mind when trying to fit such a model to observational data.…”
Section: Substructure In Simulated Uldm Halosmentioning
confidence: 95%
“…[21]. The implications of these fluctuations for local tracer velocities have been studied elsewhere [34] and they can provide a benchmark for comparing ULDM halo fluctuations to CDM substructure, as well as adding scatter to the expected velocity dispersion. We remark that these fluctuations are not captured by the semi-analytic model of ULDM halos, and that the consequences of this should be kept in mind when trying to fit such a model to observational data.…”
Section: Substructure In Simulated Uldm Halosmentioning
confidence: 95%
“…Ref. [38] showed that a dynamical analysis of a central star cluster in Eridanus-II could potentially probe ULDM up to m 10 −19 eV.…”
Section: Introductionmentioning
confidence: 99%
“…dark matter distribution, constrain WDM and FDM theories, favoring particle masses above m WDM ∼ 3 keV and m ∼ 10 −22 eV respectively [17][18][19]. The subhalo mass function may imply even higher masses [20]. However, for FDM these constraints can only be used as guidelines, being based on simulations that ignore the impact of wave effects on baryons.…”
mentioning
confidence: 99%